Theology in the Seventies - Gilkey, Langdon (Theology today, 1970)
“… predictions represent not so much a description of the future as an expression of the priorities in the predictor's mind. Thus saying what theology will be like is really saying what I think it should be like; we extrapolate the trends that we think are creative, as if history were going to go in that wise direction. A strange view of history for a biblical realist to adopt! So let us agree to transpose all our verbs. When we guess what theology will be like, we are really saying what we think it ought to be like.”